1972
DOI: 10.1128/aem.24.6.967-971.1972
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Staphylococci in a General Medical Service

Abstract: Investigation of the ecology of Staphylococcus aureus on the medical service of the Cincinnati General Hospital was carried out from 1964 to 1970. S. aureus was cultured from 1,442 patients. Overall, there was a progressive increase in the susceptibility of S. aureus to commonly used antibiotics, but not to penicillin. Hospital-acquired S. aureus remained highly resistant to all antibiotics except penicillinase-resistant penicillins. There was a progressive decline in the percentage of hospital-acquired infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1975
1975
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…As expected, the anterior nares yielded S. aureus more frequently than did the skin. Prevalence in the nose was similar to the values of about 30% or more that have been frequently reported in the literature (16,20). Of the 26 subjects from whom S. aureus was recovered on the skin, 14 (54%) also carried the organism in the nose, again indicating that there is a positive rela- ' Significantly different from controls (P < 0.05).…”
Section: Methodssupporting
confidence: 85%
“…As expected, the anterior nares yielded S. aureus more frequently than did the skin. Prevalence in the nose was similar to the values of about 30% or more that have been frequently reported in the literature (16,20). Of the 26 subjects from whom S. aureus was recovered on the skin, 14 (54%) also carried the organism in the nose, again indicating that there is a positive rela- ' Significantly different from controls (P < 0.05).…”
Section: Methodssupporting
confidence: 85%
“…Recent studies of the hospital ecology of S. aureus did not identify predominant phage types among nosocomially acquired staphylococcal infections (4,18,23,24,26). In contrast, we previously reported that a limited number of S. aureus phage types were isolated from the blood of patients from our hospital over a 1-year period (6).…”
Section: Downloaded Frommentioning
confidence: 68%
“…The introduction of phage typing to epidemiological surveys of hospitalized patients for up to 20 years demonstrated that once carriers are colonized with certain strains of S. aureus, they generally maintain that strain and become sources of infection (33). Recent studies of the hospital ecology of S. aureus did not identify predominant phage types in nosocomially acquired staphylococcal infections (9,24,(31)(32)(33). In contrast, Cross et al (11) reported that a limited number of S. aureus phage types were isolated from the blood of patients over a 1-year period.…”
Section: Discussionmentioning
confidence: 99%